Change of Paradigm in Personnel Strategy – Corporate Social Responsibility and Internal Communication - Bednárik, Jaroslav (Communication Today, 2025)
The study points at the current times, when all people have been struggling with the problems of the socialeconomic crisis; it addresses a highly topical theme, which is the issue of applying the concept of sustainable development. The aim is to obtain information about the level of internal communication and human resources management within the addressed medium-sized companies, and whether Corporate Social Responsibility with a welfare focus is also a part of the corporate culture and corporate strategy. It is necessary to point out the fact that the development of the staff is not only linked to the notion of economic growth, but needs to be directed towards the achievement of important social objectives, such as, for example, improving quality of life (both private and professional), enhancing opportunities for better education, health, etc. An important role is also played by new trends in this area, which include new types of consumers focused on changing their quality of work and personal lives, known under the expressions LOHAS (Lifestyle of Health and sustainability) or CSV – Creating Shared Value. At present, the fundamental problem is effective internal communication, which serves to handle vast amounts of everyday information, commands and tasks shared by all company employees. In-house communication should ensure regular informedness and the satisfaction of workers in the company, and creates a sense of trust and interest in them. However, the way it is set up in an organisation is extremely important; otherwise it can bring the opposite effect. This requires an understanding of the importance of internal communication and its potential for growing business performance, but also for the practical application of internal communication in the processes of management, including Corporate Social Responsibility.